Preparation method of polymer precursor derived all-inorganic super-hydrophobic coating
Through the preparation method of polymer precursor derived all-inorganic superhydrophobic coating, the problems of poor wear resistance, temperature resistance and weather resistance of traditional superhydrophobic materials are solved, and a high-temperature stability, wear resistance and corrosion resistance are achieved, and an all-inorganic superhydrophobic coating with excellent waterproofing and self-cleaning properties are achieved.
Patent Information
- Application Number
- CN202510026676.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-07
AI Technical Summary
Traditional superhydrophobic materials have problems such as poor wear resistance, poor temperature resistance, and poor weather resistance, making it difficult to show excellent performance in actual engineering applications.
The preparation method of polymer precursor-derived all-inorganic superhydrophobic coating is used to form a new Si-C-O-H hydrophobic group at high temperature by using a polysilane precursor, ethyl silicate and dibutyltin dilaurate composite catalyst to form a new hydrophobic group of Si-C-O-H at high temperature to construct an all-inorganic superhydrophobic coating.
It realizes the high temperature stability, wear resistance and corrosion resistance of the all-inorganic superhydrophobic coating, with contact angles up to 168° or above and sliding angles less than 5°, and has excellent waterproof and self-cleaning properties.
Smart Images

Figure CN119824416A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of functionalized protection of material surfaces, and in particular to a method for preparing a polymer precursor-derived all-inorganic super-hydrophobic coating. Background Art
[0002] There are many super-hydrophobic surfaces in nature, such as lotus leaves, butterfly wings, rice leaves, etc. Bionic super-hydrophobic surfaces have received widespread attention because of their potential application prospects such as self-cleaning, waterproofing, anti-icing, and anti-fogging. Usually, these super-hydrophobic materials all use organic coatings with low surface energy, such as silicone, fluorosilicone resin, etc. to modify the rough surface with micro-nano structure. However, the durability, high temperature stability and environmental adaptability of these prepared super-hydrophobic surfaces are poor. On the other hand, about inorganic super-hydrophobic coatings: Related reports on the preparation of super-hydrophobic coatings by organic-inorganic hybridization, using organic binders as low surface energy materials, also have the problem of poor temperature resistance. Patent No. CN114836725A discloses a method for preparing a low-temperature steel inorganic super-hydrophobic anti-icing coating structure, which mainly uses rare earth oxides to form a prism array to construct a hydrophobic structure. Therefore, in order to solve the problems of poor wear resistance, temperature resistance and weather resistance of traditional super-hydrophobic materials, a high-temperature resistant, wear-resistant and corrosion-resistant all-inorganic super-hydrophobic coating is prepared using polymer derivatives. The coating can greatly improve its wear resistance, temperature resistance and weather resistance and possess excellent properties such as waterproofness and self-cleaning, which has broad prospects in practical engineering applications. Summary of the invention
[0003] The purpose of the present invention is to provide a method for preparing a polymer precursor-derived all-inorganic super-hydrophobic coating, which is safe, environmentally friendly, highly practical, simple to operate, and highly designable. An all-inorganic super-hydrophobic coating is achieved on the surface of metal, glass, and ceramic materials. The contact angle of the coating can reach more than 168°, and the sliding angle is less than 5°. It has excellent high temperature resistance, wear resistance, corrosion resistance, waterproofness, and self-cleaning properties. This method provides a new idea for realizing substrate material protection and large-scale application.
[0004] To achieve the above object, the present invention provides a method for preparing a polymer precursor-derived all-inorganic super-hydrophobic coating, comprising the following steps:
[0005] Step 1: preparing metal, glass and ceramic with micro-nano surface structure, wherein the metal is one of aluminum, magnesium and titanium;
[0006] Step 2: Add polysilane precursor, ethyl silicate and dibutyltin dilaurate complex catalyst into n-hexane or n-heptane to prepare a precursor solution, stir, and immerse the material with micro-nano surface structure prepared in step 1 into the solution for 10-60 minutes;
[0007] Step 3: Place the precursor-coated material obtained in step 2 into a high-temperature furnace. The polysilane precursor coordinates with ethyl silicate to form a stable macromolecular network structure. In a non-oxygen environment, a new Si-COH hydrophobic group is formed and maintained. The fully inorganic super-hydrophobic coating is obtained by heating.
[0008] Preferably, in step one, a multi-scale porous and cauliflower-shaped micro-nano structure is prepared on the metal surface by micro-arc oxidation, and a multi-scale cauliflower-shaped or needle-shaped micro-nano structure is prepared on the glass and ceramic surface by hydrothermal, alkaline thermal, and high-pressure hydrothermal methods.
[0009] Preferably, micro-arc oxidation is to place the metal in an alkaline electrolyte, set the temperature to 30°C to 50°C, apply a voltage of 500V to 600V, a frequency of 200Hz to 1000Hz and a duty cycle of 4% to 30%, and perform micro-arc oxidation treatment on the metal surface to obtain a ceramic coating with a porous structure on the metal surface.
[0010] Preferably, the ceramic coating with a porous structure on the metal surface is treated by hydrothermal, alkaline thermal, or high-pressure hydrothermal methods to in situ grow multi-scale cauliflower-like or needle-like micro-nano structures on the surface, providing roughness and a dual-scale structure for the superhydrophobic coating.
[0011] Preferably, in step 2, the precursor solution is prepared by adding 10-50 g of polysilane precursor, 2-7 g of ethyl silicate and 1-5 g of dibutyltin dilaurate complex catalyst into 20-60 g of n-hexane or n-heptane to prepare a precursor solution, and stirring for 20-60 min.
[0012] Preferably, in step three, the high temperature furnace is heated to a temperature of 400-500° C. for a heating time of 1-4 hours.
[0013] Preferably, in step three, the non-oxygen environment in the high temperature furnace includes nitrogen, argon or vacuum.
[0014] Preferably, in step three, the all-inorganic super-hydrophobic composite coating has a thickness of 20 μm-200 μm, a contact angle ≧168°, a sliding angle <5°, and is resistant to high temperatures of 400-500°C, and can still maintain super-hydrophobicity at high temperatures of 400-500°C.
[0015] The advantages and beneficial effects of the method for preparing an all-inorganic super-hydrophobic coating derived from a polymer precursor of the present invention are:
[0016] 1. The present invention uses the method of derivatization and pyrolysis of organic precursor polymers to prepare a fully inorganic super-hydrophobic coating with a multi-scale micro-nano structure on the surface of metal, glass and ceramic materials. The method is fast, convenient, efficient, can prepare large-area special-shaped components, and has a large design space.
[0017] 2. The present invention proposes a polymer-derived all-inorganic super-hydrophobic coating that is resistant to high temperature, wear and corrosion. The coating is dense, has high surface quality and a controllable thickness of 20μm-200μm.
[0018] 3. The present invention utilizes polymer derivatives to form a high temperature resistant, wear resistant and corrosion resistant all-inorganic super hydrophobic coating, which has excellent mechanochemical stability, greatly improved wear resistance, corrosion resistance improved by more than 3 orders of magnitude, and greatly improved high temperature resistance than organic coatings, and has excellent environmental adaptability, waterproof and self-cleaning properties.
[0019] 4. The present invention utilizes polymer derivatives to form a high temperature resistant, wear resistant and corrosion resistant all-inorganic super hydrophobic coating. The coating has a multi-layer structure, and the outermost layer forms a Si-CO all-inorganic super hydrophobic layer with low surface energy methyl. The contact angle can reach more than 168°, and the sliding angle is less than 5°. It has excellent mechanochemical robustness and waterproof and self-cleaning properties, and provides a new method for realizing the protection and large-scale application of substrate materials such as metals, glass, and ceramics.
[0020] The technical solution of the present invention is further described in detail below through the drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a schematic diagram of the structure of the all-inorganic super-hydrophobic coating derived from a polymer precursor of the present invention;
[0022] Figure 2 This is a schematic diagram of the structure of a highly stable and low surface energy macromolecular network formed by the polymerization of a polysilane precursor of the present invention;
[0023] Figure 3 This is a microscopic morphology of the surface of the titanium alloy micro-arc oxidation coating in Example 1 of the present invention;
[0024] Figure 4 This is a surface microscopic morphology of the titanium alloy micro-arc oxidation hydrothermal composite coating of Example 1 of the present invention;
[0025] Figure 5 This is a surface microscopic morphology of a fully inorganic super-hydrophobic coating formed by polymer derivatization on the surface of a titanium alloy micro-arc oxidation hydrothermal composite coating in Example 1 of the present invention;
[0026] Figure 6 Schematic diagram of the static contact angle of the all-inorganic super-hydrophobic coating formed on the surface of the titanium alloy micro-arc oxidation hydrothermal composite coating by polymer derivatization in Example 1 of the present invention;
[0027] Figure 7 Schematic diagram of the rolling angle of the all-inorganic super-hydrophobic coating formed by polymer derivatization on the surface of the titanium alloy micro-arc oxidation hydrothermal composite coating in Example 1 of the present invention;
[0028] Figure 8 This is a polarization curve diagram of a fully inorganic super-hydrophobic coating formed by polymer derivatization on the surface of a titanium alloy micro-arc oxidation hydrothermal composite coating according to Example 1 of the present invention;
[0029] Fig. 9 This is a schematic diagram of the wear resistance test of the all-inorganic super-hydrophobic coating formed on the surface of the titanium alloy micro-arc oxidation hydrothermal composite coating by polymer derivatization in Example 1 of the present invention;
[0030] Fig.10 This is a contact angle variation diagram of the all-inorganic super-hydrophobic coating formed by polymer derivatization on the surface of the titanium alloy micro-arc oxidation hydrothermal composite coating in Example 1 of the present invention after wear;
[0031] Fig.11 This is a high temperature stability curve of the all-inorganic super-hydrophobic coating formed by polymer derivatization on the surface of the titanium alloy micro-arc oxidation hydrothermal composite coating in Example 1 of the present invention;
[0032] Fig.12 The microscopic morphology of the all-inorganic super-hydrophobic coating of Example 3 of the present invention, wherein (a) is the micro-nano structure on the surface of Al2O3 ceramics, and (b) is the cauliflower-like micro-nano structure on the surface of SiO2 ceramics;
[0033] Fig.13 The contact angle bar graph of the all-inorganic super-hydrophobic coating of Example 3 of the present invention;
[0034] Fig.14 This is a diagram showing the high temperature resistance of the all-inorganic super-hydrophobic coating of Example 3 of the present invention. DETAILED DESCRIPTION
[0035] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0036] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0037] Unless otherwise defined, the reagents and equipment used in the present invention are commercially available.
[0038] Example 1
[0039] A method for preparing a polymer precursor-derived all-inorganic super-hydrophobic coating comprises the following steps:
[0040] 1. Select TA15 titanium alloy as the substrate, polish the surface with 600, 800 and 1000# sandpaper in turn, and then ultrasonically clean it with anhydrous ethanol and deionized water for 10 minutes respectively.
[0041] 2. Use 12g / L sodium silicate, 8g / L sodium hexametaphosphate, and 2g / L sodium hydroxide and stir them evenly to prepare a basic electrolyte.
[0042] 3. Use stainless steel plate or stainless steel cell as cathode, TA15 titanium alloy material as anode, use the above basic electrolyte, apply 600V pulse voltage between the positive and negative electrodes, current density: 28000A / m 2 ; Time: 15 min, frequency: 500 Hz, duty cycle: 25%, the solution temperature was controlled at 30°C, and under continuous stirring conditions, a micro-arc oxidation ceramic coating was prepared with a coating thickness of 30 μm.
[0043] Fourth, the prepared micro-arc oxidation coating was subjected to hydrothermal treatment. The method is as follows: 0.1g of sodium hydroxide (NaOH), 4g of aluminum nitrate (Al(NO3)3·9H2O), and 0.2g of calcium acetate (Ca(CH3COO)2) were dissolved in 30mL of deionized water, and 0.3g of hexamethylenetetramine (C6H 12 N4) to obtain a solution. The solution was poured into a stainless steel autoclave lined with Teflon and stirred for 20 minutes with a magnetic stirrer. The micro-arc oxidation coating was then placed in the mixed solution and subjected to a hydrothermal reaction at a temperature of 150° C. for 18 hours to prepare a micro-arc oxidation hydrothermal composite layer.
[0044] 5. Add 10g of polysilane precursor, 2g of tetraethylorthosilicate (TEOS) and 1g of dibutyltin dilaurate complex (DBTDL) catalyst into 20g of n-hexane to prepare a solution, and stir for 30 minutes. Immerse the prepared micro-arc oxidation hydrothermal composite coating into the solution and keep it at room temperature for 40 minutes.
[0045] 6. The composite coating was taken out from the solution, placed in a tubular furnace, heated to 400°C in an atmosphere of 99.9% nitrogen, and kept warm for 3 hours to obtain a 60 μm thick all-inorganic super-hydrophobic coating with excellent high temperature resistance, wear resistance, and corrosion resistance.
[0046] The all-inorganic superhydrophobic coating prepared by the method of this embodiment has excellent superhydrophobic properties, a static contact angle greater than 168°, a rolling angle less than 5°, excellent mechanochemical robustness, and waterproof and self-cleaning properties, providing a new method for achieving protection and large-scale application of metal, inorganic and other substrate materials.
[0047] Figure 1 Schematic diagram of the structure of the all-inorganic super-hydrophobic coating derived from the polymer precursor of the present invention. Figure 1As shown, the preparation method can prepare a ceramic coating on the surface of a metal substrate, form a micro-nano structure after hydrothermal treatment, and form a fully inorganic super-hydrophobic coating after coating with an inorganic super-hydrophobic coating derived from a modified polymer precursor; or directly perform hydrothermal treatment or autoclave treatment on the ceramic surface to perform micro-nano structure treatment to form a multi-scale structure, and form a fully inorganic super-hydrophobic coating after modification with a polymer precursor.
[0048] Figure 2 The schematic diagram of the high stability and low surface energy macromolecular network structure formed by the reaction and polymerization of polysilane precursors. Figure 2 As shown in the figure, under the action of ethyl silicate and catalyst, linear polysilane forms a closed-loop polymerization state, and the molecular chains are entangled, the polymerization chain grows to form new active points, and the multi-active point cross-linking polymerization forms a high-stability macromolecular network structure, which can form a coordination structure to protect the hydrophobic group at high temperature to maintain long-term high-temperature stable service. In addition, by coordinating the polysilane precursor with ethyl silicate, the treatment in a vacuum or non-oxygen atmosphere can promote the polymerization of the polymer to form alkyl groups of the macromolecular chain. Such alkyl groups can remain hydrophobic at high temperatures, which is attributed to the formation of Si-COH by the ring polymerization. This composite functional group repel water molecules and produce a shielding effect, making it difficult to adsorb water molecules on the interface and showing hydrophobicity.
[0049] like Figure 3 As shown, a titanium oxide (TiO2)-based ceramic coating with a porous structure is prepared on the surface of a titanium alloy using micro-arc oxidation technology, providing a ceramic template for the subsequent formation of a micro-nano structure.
[0050] like Figure 4 As shown, a hydrothermal method is used to in situ grow special structures with micro-nano needles (aspect ratio 20:1), cauliflower shapes (diameter 1-3μm), and square shapes on the surface of the titanium oxide (TiO2)-based ceramic coating, providing roughness and micro-nano multi-scale structure for the hydrophobic / super-hydrophobic surface.
[0051] like Figure 5 As shown, a polymer precursor is coated on the surface of a micro-nano structure, and further subjected to high-temperature derivatization and transformation to form a high-temperature resistant, wear-resistant, and corrosion-resistant all-inorganic super-hydrophobic coating. The coating surface presents a multi-scale micro-nano super-hydrophobic structure, with needle-like and cauliflower-like surfaces providing a graded structure, and the polymer precursor transformation product provides a low surface energy.
[0052] like Figure 6 As shown, the surface contact angle of the all-inorganic super-hydrophobic coating was tested to be 168.9°, which has excellent ability to resist water.
[0053] like Figure 7 As shown, the surface rolling angle test of the all-inorganic super-hydrophobic coating is 5°, which has excellent ability to resist water.
[0054] like Figure 8 As shown in the figure, the corrosion potential and corrosion current density in the polarization curve are the key parameters for evaluating the corrosion resistance of the coating. The results show that compared with the substrate and single micro-arc oxidation, the all-inorganic super-hydrophobic coating has the smallest corrosion current and the highest corrosion potential, showing the best corrosion resistance. This is attributed to the fact that on the one hand, the super-hydrophobic coating hinders the direct contact between the corrosive medium and the substrate, slowing down its corrosion rate; on the other hand, the all-inorganic super-hydrophobic outer layer forms a strong sealing effect on the porous micro-arc oxidation layer, preventing the corrosive medium from penetrating the coating to corrode the substrate. In addition, the improvement of its overall density significantly enhances the corrosion resistance of the coating, which is conducive to long-term corrosion protection.
[0055] like Fig. 9 and Fig.10 As shown in the figure, the all-inorganic super-hydrophobic coating was subjected to a friction and wear test using No. 240 sandpaper, a load of 100g, and a distance of 5cm from the center of the rotating platform to the center of the sample. The results showed that after 80 friction and wear cycles, the contact angle of the coating surface was still greater than 154°, indicating that the coating has excellent wear resistance and robustness.
[0056] like Fig.11 As shown in the figure, the all-inorganic super-hydrophobic coating was placed in a high temperature environment (500℃ for 2h, 400℃ for 48h), and it was found that after 500℃ treatment for 2h, the all-inorganic super-hydrophobic coating still maintained super-hydrophobicity (contact angle>150.2°), and water droplets could roll freely on the coating surface. In an extremely high temperature environment, the all-inorganic precursor conversion and micro-nano rough structure can give the coating super-hydrophobicity. After 48h at 400℃, the coating still has super-hydrophobicity, and the contact angle is still>151°. Such a special all-inorganic precursor conversion combined with micro-nano structure gives the coating long-term high-temperature super-hydrophobic properties.
[0057] Example 2
[0058] A method for preparing a polymer precursor-derived all-inorganic super-hydrophobic coating comprises the following steps:
[0059] 1. AZ31 magnesium alloy was selected as the substrate, and the surface was polished with 800, 1000 and 1200# sandpaper in turn, and then ultrasonically cleaned with anhydrous ethanol and deionized water for 20 minutes respectively;
[0060] 2. 12g / L sodium silicate, 8g / L sodium hexametaphosphate, and 2g / L sodium hydroxide are mechanically stirred to obtain a basic electrolyte;
[0061] 3. Use stainless steel plate or stainless steel cell as cathode, AZ31 magnesium alloy material as anode, use the above basic electrolyte, apply 400V pulse voltage between the positive and negative electrodes, current density: 12000A / m 2; Time: 20min, frequency: 800Hz, duty cycle: 30%, the solution temperature was controlled at 30°C, and under continuous stirring conditions, the solution temperature was controlled at 30°C, and under continuous stirring conditions, a micro-arc oxidation ceramic coating was prepared with a coating thickness of 38μm.
[0062] Fourth, the prepared micro-arc oxidation coating was subjected to hydrothermal treatment. The method is as follows: 0.2g NaOH, 5g Al(NO3)3·9H2O, and 0.5g Ca(CH3COO)2 were dissolved in 30mL deionized water, and 0.5g C6H 12 N4, prepare a solution. Pour the solution into a Teflon-lined stainless steel autoclave and stir with a magnetic stirrer for 30 minutes. Then put the micro-arc oxidation coating into the above mixed solution and perform a hydrothermal reaction at a temperature of 180°C for 24 hours to prepare a micro-arc oxidation hydrothermal composite coating;
[0063] 5. Add 20g of polysilane precursor, 3g of TEOS and 2g of DBTDL catalyst into 38g of n-heptane to prepare a solution, and stir for 20 minutes. Immerse the prepared micro-arc oxidation hydrothermal composite coating into the solution and immerse it at room temperature for 30 minutes;
[0064] 6. The composite coating was taken out from the solution, placed in a tubular furnace, heated to 450°C in a non-oxygen atmosphere (argon), and kept warm for 4 hours to obtain a 50 μm thick all-inorganic super-hydrophobic coating with excellent high temperature resistance, wear resistance, and corrosion resistance.
[0065] The all-inorganic super-hydrophobic coating prepared by the method of this embodiment has excellent super-hydrophobic properties, a static contact angle of 169°, a rolling angle of 4°, and excellent high temperature resistance, wear resistance, corrosion resistance, waterproofness and self-cleaning properties, providing a new method for achieving the protection and large-scale application of metal, inorganic and other substrate materials.
[0066] Example 3
[0067] A method for preparing a polymer precursor-derived all-inorganic super-hydrophobic coating comprises the following steps:
[0068] 1. Select alumina (Al2O3) ceramics and silicon dioxide (SiO2) glass respectively;
[0069] Second, Al2O3 ceramics and SiO2 glass were subjected to autoclave hydrothermal treatment. The method is as follows: 0.5g NaOH, 7g Al(NO3)3·9H2O, 1.0g Ca(CH3COO)2 were dissolved in 40mL deionized water, and 0.8g C6H 12N4, and a solution was prepared. The solution was poured into a stainless steel autoclave lined with Teflon, and Al2O3 ceramics and SiO2 glass were placed in the mixed solution. A high-pressure hydrothermal reaction was carried out at a temperature of 220°C and 50MPa. After a reaction time of 36 hours, multi-scale micro-nano structures (such as Fig.12 shown).
[0070] 3. Add 40g of polysilane precursor, 6.5g of TEOS and 4g of DBTDL catalyst into 60g of n-heptane to prepare a solution, and stir for 30 minutes. Place Al2O3 ceramics and SiO2 glass with micro-nano structure in the above solution and keep at room temperature for 40 minutes to prepare a composite coating on their surface;
[0071] 4. The composite coating is taken out from the solution, placed in a tubular furnace, heated to 450°C in a non-oxygen atmosphere (N2), and kept warm for 2 hours to obtain a 70 μm thick all-inorganic super-hydrophobic coating with excellent high temperature resistance, wear resistance, and corrosion resistance.
[0072] The all-inorganic super-hydrophobic coating prepared by the method of this embodiment has excellent super-hydrophobic properties. Fig.13 As shown in Figure 2, the static contact angle of the coating is >169°. Fig.14 As shown, the coating exhibits excellent high temperature resistance of 500°C, which provides ideas for the application of superhydrophobic coatings in high temperature environments. At the same time, the composite coating has good waterproof and self-cleaning properties, providing a new method for realizing the protection and large-scale application of inorganic matrix materials.
[0073] At present, super hydrophobic coatings are mainly organic coatings, mainly using hydrocarbon groups and ester groups: such as C10~C20 hydrocarbon groups; hydrocarbon groups containing aromatic groups, esters, ethers, amines, amides and other groups; polyoxypropylene groups, long-chain perfluoroalkyl groups, etc. These materials all have low surface energy, but at high temperatures, whether CH or CF, pyrolysis occurs, and even volatilization causes hydrophobic group destruction, which is difficult to apply at high temperatures. A novel hydrophobic group Si-COH proposed by the present invention, due to the formation of a high-stability macromolecular network structure, can form a coordination structure protecting the hydrophobic group at high temperatures, ensuring long-term high-temperature service. On the other hand, the coating is coordinated with ethyl silicate by a polysilane precursor, and the alkyl group that promotes polymer polymerization to form a macromolecular chain is processed in a vacuum or non-oxygen atmosphere, which not only ensures the high-temperature service stability of the coating, but also can still maintain hydrophobicity or even super-hydrophobicity at high temperatures, which is of great significance for super hydrophobic coatings to serve for a long time at high temperatures. In addition, the coating can be made into a coating or adhesive through molecular scale design and widely used on the surfaces of different materials. The preparation method is simple and practical. It is expected to be widely used in high-temperature components, especially aircraft surfaces for waterproofing and anti-icing in the future.
[0074] Therefore, the present invention adopts the above-mentioned method for preparing a polymer precursor-derived all-inorganic super-hydrophobic coating, which is safe, environmentally friendly, practical, simple to operate, and highly designable. A fully inorganic super-hydrophobic coating is realized on the surface of metal, glass, and ceramic materials. The contact angle of the coating can reach more than 168°, and the sliding angle is less than 5°. It has excellent high temperature resistance, wear resistance, corrosion resistance, waterproofness and self-cleaning properties. This method provides a new idea for realizing substrate material protection and large-scale application.
[0075] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a polymer precursor-derived all-inorganic super-hydrophobic coating, characterized in that: The steps include: Step 1: preparing metal, glass and ceramic with micro-nano surface structure, wherein the metal is one of aluminum, magnesium, titanium and alloys thereof; Step 2: Add polysilane precursor, ethyl silicate and dibutyltin dilaurate complex catalyst into n-hexane or n-heptane to prepare a precursor solution, stir, and immerse the material with micro-nano surface structure prepared in step 1 into the solution for 10-60 minutes; Step 3: Place the precursor-coated material obtained in step 2 into a high-temperature furnace. The polysilane precursor coordinates with ethyl silicate to form a stable macromolecular network structure. In a non-oxygen environment, a new Si-COH hydrophobic group is formed and maintained. The fully inorganic super-hydrophobic coating is obtained by heating.
2. The method for preparing a polymer precursor-derived all-inorganic super-hydrophobic coating according to claim 1, characterized in that: In step one, a multi-scale porous and cauliflower-like micro-nano structure is prepared on the metal surface by micro-arc oxidation, and a multi-scale cauliflower-like or needle-like micro-nano structure is prepared on the glass and ceramic surface by hydrothermal, alkaline thermal, and high-pressure hydrothermal methods.
3. The method for preparing a polymer precursor-derived all-inorganic super-hydrophobic coating according to claim 2, characterized in that: Micro-arc oxidation is to place the metal in an alkaline electrolyte, set the temperature to 30℃~50℃, apply a voltage of 500V~600V, a frequency of 200Hz~1000Hz and a duty cycle of 4%~30%, and perform micro-arc oxidation treatment on the metal surface to obtain a ceramic coating with a porous structure on the metal surface.
4. The method for preparing a polymer precursor-derived all-inorganic super-hydrophobic coating according to claim 3, characterized in that: The ceramic coating with a porous structure on the metal surface is treated by hydrothermal, alkaline thermal, and high-pressure hydrothermal methods to in situ grow multi-scale cauliflower-like or needle-like micro-nano structures on the surface, providing roughness and dual-scale structure for the superhydrophobic coating.
5. The method for preparing a polymer precursor-derived all-inorganic super-hydrophobic coating according to claim 1, characterized in that: In step 2, the precursor solution is prepared by adding 10-50 g of polysilane precursor, 2-7 g of ethyl silicate and 1-5 g of dibutyltin dilaurate complex catalyst into 20-60 g of n-hexane or n-heptane to prepare a precursor solution, and stirring for 20-60 min.
6. The method for preparing a polymer precursor-derived all-inorganic super-hydrophobic coating according to claim 1, characterized in that: In step 3, the high temperature furnace is heated to 400-500° C. for 1-4 hours.
7. The method for preparing a polymer precursor-derived all-inorganic super-hydrophobic coating according to claim 1, characterized in that: In step three, the non-oxygen environment in the high temperature furnace includes nitrogen, argon, and vacuum.
8. The method for preparing a polymer precursor-derived all-inorganic super-hydrophobic coating according to claim 1, characterized in that: In step three, the thickness of the all-inorganic super-hydrophobic composite coating is 20 μm-200 μm, the contact angle is ≧168°, the sliding angle is <5°, and it is resistant to high temperatures of 400-500°C.
Citation Information
Patent Citations
Inorganic super-hydrophobic anti-icing coating structure for low-temperature steel and preparation method thereof
CN114836725A
Super-hydrophobic powder material as well as preparation method and application thereof
CN116410629A
Method for preparing super-hydrophobic composite film layer on surface of magnesium alloy
CN118127596A
Antagonistic microorganisms having activity against plant pathogens and plant diseases controlling agent comprising the same
KR102718012B1